2021
DOI: 10.21037/tlcr-21-603
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive severe immune-related adverse events after PD-1 inhibitor induction and surgery in locally advanced non-small cell lung cancer: a case report

Abstract: Neoadjuvant PD-(L)1 inhibitors may be promising for locally advanced non-small cell lung cancer (NSCLC) with potential pathological and survival benefits. But severe immune-related adverse events (irAEs) may cause fatal consequences which require early identification and timely intervention. The basis for most of these adverse events is a reactive hyperactivated T-cell response to normal tissues that results in the production of high levels of CD4 T-helper cell cytokines or increased migration of cytolytic CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…As immune-related adverse events typically have a delayed onset and prolonged duration, postoperative immune-related pneumonia should not be overlooked. Zhao et al reported the occurrence of immune-related pneumonia one week after surgery in a patient with locally advanced non-small cell lung cancer who underwent neoadjuvant immunotherapy; the patient recovered with timely intervention with corticosteroids [ 20 ]. However, few studies have reported postoperative immune-related pneumonia in patients with ESCC and similarly, none of our patients experienced immune-related pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…As immune-related adverse events typically have a delayed onset and prolonged duration, postoperative immune-related pneumonia should not be overlooked. Zhao et al reported the occurrence of immune-related pneumonia one week after surgery in a patient with locally advanced non-small cell lung cancer who underwent neoadjuvant immunotherapy; the patient recovered with timely intervention with corticosteroids [ 20 ]. However, few studies have reported postoperative immune-related pneumonia in patients with ESCC and similarly, none of our patients experienced immune-related pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…PiggyBac transposon vectors are the most popular transposon-based vectors in cell reprogramming. [128,154] These vectors make deletion and insertion of a specific gene code possible by cutting and pasting their gene code cargo. [153] PiggyBac transposon has some advantages including a safe gene delivery due to its "footprint-free excision" character, convenient production process, high transposition activity because of its superior [19,102,139,147] Sonoporation (Figure 3b)…”
Section: Biological Vectors In Nonviral Cell Reprogrammingmentioning
confidence: 99%
“…• Low throughput [149,135] Microfluidic (Figure 3e) Microfluidic with channels smaller than the diameter of the cell causes cell membrane deformation and increases the permeability of cells to intake reprogramming factors in the surrounding buffer packaging capacity, as well as the high transposition efficiency in a vast range of organisms from yeasts to mammals. [154,155] It should be noted that transposons should be combined with a plasmid to be able to enter the cells. CRISPR/Cas9 gene editing tools represent another class of biological vectors composing a nucleus named Cas9 and a guide RNA.…”
Section: Biological Vectors In Nonviral Cell Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trial data and literatures suggest that irAEs in NSCLC immunotherapy mainly involve the cardiac, pulmonary, gastrointestinal, endocrine, dermatologic and nervous system damage (8)(9)(10)(11). While the majority of cases are mild and tolerable, some of them can present with moderate to severe toxicities, which are related to decreased organic function, as well as poor quality of life (12)(13)(14). A study showed that the overall incidence of irAEs of any grade in patients with NSCLC was 30%, with a severe grade of 6% (15).…”
Section: Introductionmentioning
confidence: 99%